2022
DOI: 10.1002/adfm.202205255
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Hydrogen Permeability of Mixed Protonic–Electronic Conducting Membranes through an In‐Situ Exsolution Strategy

Abstract: Mixed protonic–electronic conducting (MPEC) ceramic membranes with high H2 permeability and stability are significant for practical H2 separation. CO2‐tolerant lanthanum tungstate oxides have received much attention, but their low H2 permeability is their main problem for membrane applications. Herein, an efficient in‐situ exsolution strategy is proposed to enhance the H2 permeability and CO2 stability of lanthanum tungstate‐type membranes. During H2 permeation, the catalytic Pd nanoparticles are in‐situ gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Therefore, the processes in Equations () and () were greatly enhanced with the removal of O 2− , resulting in the most detected H 2 permeation flux. It can be seen that the influence of steam on the H 2 permeation of materials at the sweep side and the feed side was consistent with literature reports 48–50 . Then, the long‐term stability of BCFe and BCFeP 0.05 membranes at 950°C under humidification at the sweep side (condition (i)) was studied, as shown in Figure 4c.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, the processes in Equations () and () were greatly enhanced with the removal of O 2− , resulting in the most detected H 2 permeation flux. It can be seen that the influence of steam on the H 2 permeation of materials at the sweep side and the feed side was consistent with literature reports 48–50 . Then, the long‐term stability of BCFe and BCFeP 0.05 membranes at 950°C under humidification at the sweep side (condition (i)) was studied, as shown in Figure 4c.…”
Section: Resultssupporting
confidence: 87%
“…It can be seen that the influence of steam on the H 2 permeation of materials at the sweep side and the feed side was consistent with literature reports. [48][49][50] Then, the long-term stability of BCFe and BCFeP 0.05 membranes at 950 • C under humidification at the sweep side (condition (i)) was studied, as shown in Figure 4c. Compared to the parent BCFe membrane, the partial conductivity of protons and electrons of the representative BFCeP 0.05 was slightly decreased after the partial substitution of Fe site with P (Figure S12a).…”
Section: Resultsmentioning
confidence: 99%
“…The anchoring of metal nanoparticles on the grain surface reduces the migration path for electron conduction, enhancing both electron conductivity and catalytic processes. 10,[19][20][21][22][23]33,34 The microscopic morphology of BZCYYbFe powder remained largely unchanged after hydrogen treatment under a reducing atmosphere, indicating the stable presence of Fe within the lattice without any exsolution occurring, as shown in Figure 3C. It has been reported that the exsolution of metallic elements under reducing atmo-spheres is influenced not only by the reducibility of material, but also by the concentration of oxygen vacancies surrounding them; 35 a higher concentration of oxygen vacancies (lower coordination number) tends to promote such exsolution.…”
Section: Results and Discussion Powders And Membranes Characteristicsmentioning
confidence: 99%
“…In this study, we investigated the correlation between enhanced hydrogen separation performance and the exsolution of metal nanoparticles. For this purpose, we doped Fe, Co, and Ni elements, known for their catalytic effects, 22 into the B-site of the BZCYYb perovskite structure. This doping aimed to enhance electronic conductivity and promote hydrogen separation.…”
Section: Introductionmentioning
confidence: 99%
“…The solid-state reaction (SSR) method was used for synthesizing LSFT and La 0.6 Sr 0.4 Fe 0.9 Nb 0.1 O 3− δ (LSFN) powders for a low cost and simple preparation process. 27–29 The raw chemical agents used are analytically pure La 2 O 3 , SrCO 3 , Fe 2 O 3 , Ta 2 O 5 and Nb 2 O 5 . BZCYYb powders were prepared by the sol–gel method.…”
Section: Methodsmentioning
confidence: 99%